Impact on Antibiotic Resistance, Therapeutic Success, and Control of Side Effects in Therapeutic Drug Monitoring (TDM) of Daptomycin: A Scoping Review - Carolina Osorio; Laura Garzón; Diego Jaimes; Edwin Silva; Rosa-Helena Bustos (MDPI AG, 2021)
Antimicrobial resistance (AR) is a problem that threatens the search for adequate safe and effective antibiotic therapy against multi-resistant bacteria like methicillin-resistant Staphylococcus aureus (MRSA), and vancomycin-resistant Enterococci (VRE) and Clostridium difficile, among others. Daptomycin is the treatment of choice for some infections caused by Gram-positive bacteria, indicated most of the time in patients with special clinical conditions where its high pharmacokinetic variability (PK) does not allow adequate plasma concentrations to be reached. The objective of this review is to describe the data available about the type of therapeutic drug monitoring (TDM) method used and described so far in hospitalized patients with daptomycin and to describe its impact on therapeutic success, suppression of bacterial resistance, and control of side effects. The need to create worldwide strategies for the appropriate use of antibiotics is clear, and one of these is the performance of therapeutic drug monitoring (TDM). TDM helps to achieve a dose adjustment and obtain a favorable clinical outcome for patients by measuring plasma concentrations of an administered drug, making a rational interpretation guided by a predefined concentration range, and, thus, adjusting dosages individually.